Penerapan Pembelajaran Kooperatif Model Jigsaw untuk Meningkatkan Hasil Belajar IPAS di Kelas IV SDN 066049 Medan Helvetia - Regina Sipayung; Aliyah Rumini Larasati; Fadhillah Rahma Purba; Intan Y Bintang; Litani Fivetrin Siregar; Raudhatun Najmi; Regina Kristin Manalu (Departement of Mathematics Education, 2025)
This research was conducted at SDN 066049 Jalan Mawar Raya, Helvetia Tengah, Medan Helvetia District, Medan City, North Sumatra. The population in this study was 18 students in class IV of SDN 066049 Medan with samples taken using Purpose Sampling. The data analysis used in this research is quantitative descriptive. The results of the research show that: (1) Data from pre-cycle tests that have been carried out show that the average student learning outcome is 53.33 with a level of completion reaching 22.22% 2) In cycle I, the Jigsaw learning model is implemented and tests are carried out on at the end of the cycle with learning completeness results reaching 61.11% 3) From the results of cycle II activities, the results of student learning tests with a completeness level reached 94.4%. From the results of the Cycle I and Cycle II activities that have been carried out, the application of the Jigsaw type Cooperative Learning Model can improve the learning outcomes of class IV at SDN 066049 Medan Helvetia for the 2024/2025 academic year.